A Typological Approach to the Harem Plans of the Historical Mosques in Sille - Bademci, Fikret (Fırat University, 2023)
Sille has been home to many civilisations in the historical process. For this reason, Sille has many cultural heritage from mosques to churches. Especially, there are many historical mosques in Sille, where Muslim communities lived for many years. These mosques reflect the architectural understanding of the period they were built. Thus, the mosques contribute to the development of Islamic architecture with their construction systems, workmanship and ornaments. Typological studies on these mosques are important in terms of shedding light on both Islamic architecture and Ottoman mosque architecture. The study aims to determine the typological similarities by examining the harem plans of the historical mosques in Sille. The scope of the study consists of Ak Mosque, Subaşı Mosque, Çay Mosque, Karataş Mosque, Mormi Mosque and Mezaryaka Mosque, which are the historical mosques that have survived to the present day in Sille Historical City of Selçuklu District of Konya. For the typology study, a catalogue containing the identification information, harem information, visuals and plan of a building was created. These catalogues were filled in on site by visiting the building. As a result of the study, many typological features were identified in the harim sections of the historical mosques in Sille.

Sille, tarihsel süreç içerisinde birçok medeniyete ev sahipliği yapmıştır. Bu nedenle Sille camiden kiliseye birçok kültürel mirasa sahiptir. Özellikle, Müslüman toplumların uzun yıllar yaşadığı Sille’de birçok tarihi cami bulunmaktadır. Bu camiler yapıldıkları dönemin mimari anlayışlarını yansıtmaktadırlar. Böylece camiler gerek yapım sistemleri gerek işçilikleri gerekse de süslemeleriyle İslam mimarisinin gelişimine katkı sağlamaktadır. Bu camiler üzerinde yapılacak olan tipoloji çalışmaları hem İslam mimarisine hem de Osmanlı dönemi cami mimarisine ışık tutması bakımından önemlidir. Çalışma, Sille’de bulunan tarihi camilerin harim planlarının incelenerek tipolojik benzerliklerin tespit edilmesini amaçlamaktadır. Çalışmanın kapsamını Konya’nın Selçuklu İlçesi’ne bağlı Sille Tarihi Kenti’ndeki günümüze ulaşmış tarihi camiler olan Ak Cami, Subaşı Cami, Çay Cami, Karataş Cami, Mormi Cami ve Mezaryaka Camileri oluşturmaktadır. Tipoloji çalışması için yapının künye bilgilerini, harim bilgilerini ve planını içeren bir katalog oluşturulmuştur. Bu kataloglar yapıya gidilerek yerinde doldurulmuştur. Çalışma sonucunda Sille’deki tarihi camilerin harim bölümlerinde birçok tipolojik özellik tespit edilmiştir.
Sille’de Bulunan Tarihi Camilerin Harim Planlarına Tipolojik Bir Yaklaşım
Keywords: Architectural Heritage and Conservation; Mimari Miras ve Koruma; Protection; Restoration and Repair in Buildings; Environment; Habitation and Products; Yapı; Çevre; Yerleşim ve Ürünlerde Koruma; Restorasyon; Yenileme